Natalie's winter wonderland - Norton, Liss (London: Stripes, 2011)
Natalie normally has to hibernate each winter, but this year, she's determined to stay awake long enough to have fun with her friends. She is desperate to go sledging and join in with the annual snow-animal building competition. Then she learns from her grandma that once, many years ago, she stayed up all winter
Keywords: Children's stories